Strain and crystallographic identification of the helically concaved gap surfaces of chiral nanoparticles - Sungwook Choi; Sang Won Im; Ji-Hyeok Huh; Sungwon Kim; Jaeseung Kim; Yae-Chan Lim; Ryeong Myeong Kim; Jeong Hyun Han; Hyeohn Kim; Michael Sprung; Su Yong Lee; Wonsuk Cha; et al. (Nature Communications)
Abstract Identifying the three-dimensional (3D) crystal plane and strain-field distributions of nanocrystals is essential for optical, catalytic, and electronic applications. However, it remains a challenge to image concave surfaces of nanoparticles. Here, we develop a methodology for visualizing the 3D information of chiral gold nanoparticles ≈ 200 nm in size with concave gap structures by Bragg coherent X-ray diffraction imaging. The distribution of the high-Miller-index planes constituting the concave chiral gap is precisely determined. The highly strained region adjacent to the chiral gaps is resolved, which was correlated to the 432-symmetric morphology of the nanoparticles and its corresponding plasmonic properties are numerically predicted from the atomically defined structures. This approach can serve as a comprehensive characterization platform for visualizing the 3D crystallographic and strain distributions of nanoparticles with a few hundred nanometers, especially for applications where structural complexity and local heterogeneity are major determinants, as exemplified in plasmonics.